Método de irrigação localizada de baixa pressão com sistema de cápsulas porosas como emissor - Felicio, Pedro Idelano de Alencar (2019)
The present work proposes to contributeto the study of techniques to reduce the use of water in agriculture througha localized irrigation system with porous capsule as emitter, no risk ofinterfering with the physiology of the plant or reducing its fruit production. The work consists of threechapters, as it is understood that this form is more appropriate and of fundamental importance in the development of ideas. The first chapter deals with the use of literature on the use of irrigation in the state of Ceará and the use of porous capsules inagriculture, organizing ideas and theories based on aspects related to localized irrigation and the flow of water in the soil. The second chapter deals specifically with the evaluation of the porous capsules for use as emitter. For this purpose, ten porous capsules were used to demonstrate their heterogeneity. In several aspects, among these, it is possible to emphasize the bubbling pressure test, hydraulic conductance and transudation. To better understand the physical microstructure of the capsules, nanotechnology was used, using the Scanning Electron Microscope, with a resolution of 1 nm, increasing the size of the fissures of the capsules by up to 50,000 times. As for the results, the average bubbling pressure was 2.34 atm, while the conductance presented values of 9.27 x 10-6cm² s-1. It can be observed, through the use of the microscope, that the cracks in the capsules are totally different, proving their heterogeneity. The recommendation of the use of porous capsules as emitters for localized irrigation is that they have low values of hydraulic conductance (1.50 x 10-5cm²s-1) and high bubbling pressure (2.5 atm), constituting a determining criterion for the system to function with adequate uniformity. The third chapter deals with the formation ofthe wet bulb resulting from the action of the water flow that goes through the capsule walls, observing the feed pressures applied the volume of water consumed in the bulb formation, in the unit of time, the pressures in kPa found inside the bulb, among other not less important observations, made explicit in the development of thechapter. The fourth chapter deals with the elaboration of an irrigation system via porous capsules for irrigation in the radish crop, for the proposed irrigation system, ten porous capsules were used in the execution of the experimental test, which consisted of a completely randomized design with three treatments, consisting of different irrigation managements (management via climate, via soil and via porous capsule) with 10 replications, totaling 30 experimental units. The following production parameterswere evaluated: fresh and dry matter of shoot, root and length of plants. For the study culture, no differences were observed between the treatments studied, where the fresh rootmass presented values of 7.4 g plant-1for the management via climate and 4.7 g plant-1for the management via porous capsule, and were not statistically different by the Tukey test (p <0.05). Therefore, it is concluded that the use of irrigation systems by porous capsules is an alternative for the cultivation of vegetables in small areas due to their low pressure and easy handling.